POLYGAMY IN THE LAW OF THE REPUBLIC OF INDONESIA NUMBER 1 OF 1974 AND THE EGYPTIAN FAMILY LAW NUMBER 100 OF 1985 FROM THE PERSPECTIVE OF ISLAMIC LAW AND MAQASHID SHARIA - Irsan; Koto, Alaiddin; Jamal, Khairunnas (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
ndonesia is currently in a state of emergency for adultery. The National Commission on Human Rights of the Republic of Indonesia, on its official website (2019), informs that the number of commercial sex workers (PSK) in Indonesia reaches around 230,000 people. This condition should be of concern to the government as a regulator. This research aims to analyze and compare the polygamy regulations in the Law of the Republic of Indonesia Number 1 of 1974 and the Egyptian Family Law Number 100 of 1985 from the perspective of Islamic law and maqashid sharia. This research is library research. The data analysis technique in this research is content analysis and comparison. This research concludes that first, in the polygamy regulations in Indonesia, there are requirements that are very difficult to fulfill by most husbands who want to be polygamous, namely that the court only grants permission to be polygamous if the first wife or wives are in an incurable disability or illness, cannot bear offspring, and must be with the consent of the first wife or wives. Meanwhile, the polygamy regulations in Egypt include requirements that can generally be fulfilled by husbands who want to practice polygamy, namely that they only have to explain their marital status in the marriage certificate, make a statement letter including the names of their wives and their places of residence, and the notary must notify the first wife about the new marriage. Then, polygamy can be carried out officially without permission from the court. Second, the polygamy regulations in Indonesia and Egypt are basically both built on maslahah considerations, but what distinguishes the two is that in the polygamy regulations in Indonesia there are provisions, as mentioned above, are not relevant to Islamic law because the potential harm that will arise is greater than the maslahah that will be achieved. The polygamy regulations in Egypt are all relevant to Islamic law. Third, the polygamy regulations in Indonesia and Egypt are basically both able to facilitate the realization of maqashid sharia, but what distinguishes the two is that in the polygamy regulations in Indonesia there are provisions, as mentioned above, that can hinder the process of realizing two maqashid sharia, namely protecting religion and offspring. The provisions of polygamy in Egypt are all relevant to maqashid sharia, especially in terms of protecting religion and protecting offspring. The theory found in this research is kullu tanzhimin mabniyyin 'ala al-masya'ir wahdaha, fa-inna mafsadatahu takunu a'zham min al-mashlahah al-murad tahqiquha (every regulation that is built on the consideration of feelings alone, then the mafsadah will be greater than the maslahah to be achieved). This theory is strengthened by the finding that 73.01% of polygamy requests in Indonesia were rejected, even though 34.8% of them were approved by the old wives.